A rare combination of MODY5 and duodenal atresia in a patient: a case report - Tao Du; Nan Zeng; Xiaofang Wen; Peizhuang Zhu; Wangen Li (BMC, 2020)
Abstract Background Maturity-onset diabetes of the young (MODY) is a genetically and clinically heterogeneous group of hereditary diabetes, generally caused by one abnormal gene. MODY5 is caused by mutations of the hepatocyte nuclear factor 1 homeobox β gene (HNF1β), always as a part of Chr17q12 deletion, whereas heterozygous mutation in B lymphocyte kinase (BLK) gene is responsible for MODY11. Case presentation We report a patient who developed diabetes with a 1.58-Mb Chr17q12 microdeletion and BLK gene c.211G > A mutation using the cytoscan high-density array and whole-exome sequencing analysis. The patient received the surgery at five days after birth for the duodenal atresia and had normal growth postoperatively. Mild elevated liver enzymes were found along with the normal renal function. Quantitative analysis of β-cell function markers, including fasting insulin (< 0.2 mIU/L), fasting C-peptide (0.02 μg/L), postprandial-2 h insulin (< 0.2 mIU/L), and postprandial-2 h C-peptide (0.03 μg/L) suggested a severe loss of insulin secreting capacity. Meanwhile, islet autoantibodies (GADA, IA-2, ICA, and IAA) in the patient's blood appeared negative. Neither dysplasia in other tissues nor abnormality in development and behavior was found. Conclusion To date, gastrointestinal malformations were extremely rarely reported in patients with MODY. Our clinical report further expands the clinical presentation and variability of MODY5.